Convergence Analysis of Morley Element on Anisotropic Meshes (Journal of Computational Mathematics, 2006)
The main aim of this paper is to study the convergence of a nonconforming triangular plate element-Morley element under anisotropic meshes. By a novel approach, an explicit bound for the interpolation error is derived for arbitrary triangular meshes (which even need not satisfy the maximal angle condition and the coordinate system condition ), the optimal consistency error is obtained for a family of anisotropically graded finite element meshes.
Keywords: Anisotropic meshes; Interpolation error; Consistency error; Morley element.